2007
DOI: 10.1074/jbc.m610126200
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Twin Arginine (Tat) Mutant Translocases Possessing Relaxed Signal Peptide Recognition Specificities

Abstract: The twin arginine (Tat) secretion pathway allows the translocation of folded proteins across the cytoplasmic membrane of bacteria. Tat-specific signal peptides contain a characteristic amino acid motif ((S/T)RRXFLK) including two highly conserved consecutive arginine residues that are thought to be involved in the recognition of the signal peptides by the Tat translocase. Here, we have analyzed the specificity of Tat signal peptide recognition by using a genetic approach. Replacement of the two arginine residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(125 citation statements)
references
References 33 publications
13
112
0
Order By: Relevance
“…A first, superficial targeting step would not exclusively depend on an intact RR pair, if it involved recognition of an extended sequence area within an RR signal peptide. Along this line, the recent isolation of distinct suppressor mutants in tatB and tatC that tolerate a KQ signal peptide and retain the ability to accept the RR wild type (17) suggests a large binding pocket with multiple contact points. Furthermore, less strictly conserved residues of the SRRxFLK consensus sequence likely contribute to the specificity of targeting (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first, superficial targeting step would not exclusively depend on an intact RR pair, if it involved recognition of an extended sequence area within an RR signal peptide. Along this line, the recent isolation of distinct suppressor mutants in tatB and tatC that tolerate a KQ signal peptide and retain the ability to accept the RR wild type (17) suggests a large binding pocket with multiple contact points. Furthermore, less strictly conserved residues of the SRRxFLK consensus sequence likely contribute to the specificity of targeting (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…We would predict that this recognition occurs deeper in the membrane. Recent findings indicate that an RR signal peptide must be able to interact with TatBC also within the plane of the lipid bilayer: some suppressor mutations of a KQ variant of TorA-MalE map to the N terminus of TatB predicted to lie on the trans-side of the membrane (17) as well as to a predicted periplasmic loop of TatC (18). Substitution of Phe for Val two residues downstream of the RR pair of the thylakoid precursor tOE17 results in a protease-resistant insertion of the signal sequence into the thylakoid Hcf106-cpTatC receptor (50), which together with other results prompted these authors to suggest a similar two-stage binding model.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a search for tatC mutants that allow export of a defective ssTorA(KQ)-MBP fusion, Kreutzenbeck et al reported the isolation of the amino acid substitution E8K located at the N terminus of TatB, a domain that is predicted to be localized in the periplasm. 12 The finding that mutations in periplasmic residues in TatC or in TatB can impact the recognition of the signal sequence highlights the complexity of the organization of the Tat translocon. As has been noted by Kreutzenbeck et al, mutations in residues exposed to the periplasmic side could result in a reorganization of the tertiary structure of TatC or TatB.…”
Section: Discussionmentioning
confidence: 99%
“…To test if the Tat-like targeting signal is functional we analyzed the import and assembly of a mutated Rip protein. We mutated the potential Arabidopsis Rip Tat signal of KR to QQ; glutamines were chosen because substitutions with glutamines had previously been shown to completely abolish Tat pathway export in bacteria (Kreutzenbeck et al, 2007). Using in vitro import assays into isolated Arabidopsis mitochondria it was observed that Rip-KR imports and assembles into complex III and the super-complex of I and III very efficiently, as seen by the increase in radioactive signal over time (Fig.…”
Section: The Arabidopsis Rip Protein Requires a Tat Signal And A δPh mentioning
confidence: 99%